Comparision of the Spirometric Measurements of Multi-National Under-graduate Medical Students from a Medical College of Central Nepal - Timilsina, Sameer; Karki, Sirisa; Baskota, Bhuwan (Journal of College of Medical Sciences-Nepal, 2019)
Background: The application of pulmonary function testing is increasing in many areas of clinical medicine, including assessment of airflow limitation, diagnosis of airflow obstruction and lung restriction, evaluation of pulmonary impairment, preoperative assessment as well as public health screening. In this study, attempt has been made to evaluate Pulmonary Function Test (PFT) of healthy Nepalese young adults and compare their values with healthy Indian and Sri Lankan counterparts. Further, it tries to shed light on the correlation of these data with anthropometric parameters. Methods: A total of 133 pre-clinical medical students of Manipal College of Medical Sciences were included in the study. PFT was done using a computerized automatic spirometer. Results: All the pulmonary parameters showed significant gender differences. All mean value of PFT parameters were higher in males. The comparisons of different parameters of PFT according to gender between three countries namely Nepal, India and Sri Lanka showed that Nepalese and Indian females had a higher FEV1 and FVC values than Sri Lankan females (p<0.05). Sri Lankan females had lower FEV1 and FVC as compared to Nepalese and Indian females (p<0.05). However, no correlation was observed between PFTs and BMI. Conclusions: Although some significant differences on PFT parameters were observed in Sri Lankan data when compared with Nepalese and Indian data, no significant difference was noticed between Nepalese and Indian values of PFT. Therefore Indian prediction equation for PFT can be used for Nepal but only after further study with a larger sample size.